Parent and child weight status predict weight-related behavior change. (1st July 2013) - Leary, Janie M; Ice, Christa L; Neal, William A; Cottrell, Lesley
Abstract : With the continued childhood obesity epidemic, it is vital to understand how family members influence health-related behavior change. Objective Assess associations between parent/child weight-related variables and health-related behavior change. Methods School-based screening of child weight and parent-reported health survey. Results Child behavior change was influenced by accuracy of parent perceived child weight. Parent behavior change was primarily influenced by concern about own weight. Parents accurately perceiving their children as overweight were more likely to make changes than parents with inaccurate perceptions. Conclusions Health promotion programs should incorporate parent accuracy of child and concern for own weight.